Organocatalytic sequential alpha-amination/corey-chaykovsky reaction of aldehydes: a high yield synthesis of 4-hydroxypyrazolidine derivatives - Kumar, B. Senthil; Venkataramasubramanian, V.; Sudalai, Arumugam (Organic Letters, 2012)
A tandem reaction of in situ generated a-amino aldehydes with dimethyloxosulfonium methylide under Corey-Chaykovsky reaction conditions proceeds efficiently to give 4-hydroxypyrazolidine derivatives in high yields with excellent enantio- and diastereoselectivities. This organocatalytic sequential method provides for the efficient synthesis of anti-1,2-aminoalcohols, structural subunits present in several bioactive molecules as well.

Concise synthesis of (+/-)-clopidogrel via carboxylation of benzylamine with CO2 - Venkataramasubramanian, V.; Sudalai, Arumugam (Synthetic Communications, 2015)
A concise and efficient synthesis of (+/-)-clopidogrel, an antithrombotic agent, is achieved by inserting CO2 at the benzylic position as the key reaction without using any toxic transition metals. The overall yield of the synthetic process is 38% and the salient features include operationally simple process chemistry and fewer steps.
Keywords: Antithrombatic agent; clopidogrel; CO2 insertion; Plavix

Enantioselective synthesis of guggultetrol and D-ribo-phytosphingosine tetraacetate via L-proline catalyzed sequential alpha-aminooxylation/Horner-Wardsworth-Emmons olefination-Sharpless asymmetric dihydroxylation strategy - Venkataramasubramanian, V.; Kumar, B. Senthil; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient enantioselective synthesis of two bioactive molecules, that is, guggultetrol and D-ribo-phytosphingosine, is described with high enantioselectivity (>98% ee) starting from commercially available 1-hexadecanol. The synthesis comprises organocatalyzed sequential alpha-aminooxylation of an aldehyde followed by Horner-Wardsworth-Emmons olefination and Sharp less asymmetric dihydroxylation as the key chiral inducing steps. For both syntheses, gamma-hydroxy-alpha,beta-unsaturated ester serves as the common intermediate obtained from proline catalysis. (C) 2015 Elsevier Ltd. All rights reserved.

Proline-catalyzed alpha-aminooxylation of beta-amino aldehydes: access to enantiomerically pure syn- and anti-3-amino-3-aryl-1,2-alkanediols - Venkataramasubramanian, V.; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Synlett, 2015)
A new synthetic method for enantioselective synthesis of syn 3-amino-3-aryl-1,2-alkanediols via praline catalyzed alpha-aminaoxn y ylation of beta-amino aldehydes des are described. This methodology is successfully applied to a concise and protecting group-free asymmetric synthesis of (-)-cytoxazone (+)-epi-cytoxazone and formal synthesis of N-thiolated 2-oxazolidinone.
Keywords: amino aldehydes; Asymmetric synthesis; catalysis; diastereoselectivity; Enantioselectivity; Natural product

Concise enantioselective synthesis of (+)-sertraline and (-)-CP-52002 using proline catalysis - Kalshetti, Rupali G.; Venkataramasubramanian, V.; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (+)-sertraline and its C-4 epimer (-)-CP-52002 with an overall yield of 30%, respectively, as its hydrochloride has been described. The key steps are the proline catalyzed Mannich reaction of acetaldehyde and acid catalyzed intramolecular Friedel-Crafts' alkylation reaction of olefin proceeding with high optical purities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indatraline; Mannich reaction; Proline catalysis; Sertraline; Tametraline